Ion mobilities and microscopic dynamics in liquid (Li,K)Cl. - Morgan, B; Madden, P (2004)
The dynamical properties of ionic melts formed from mixtures of LiCl and KCl have been studied across the full composition range in computer simulations of sufficient length to enable reliable values for such collective transport coefficients as the viscosity, conductivity, and internal mobilities to be determined reliably. Interest centers on the nontrivial concentration dependence exhibited by these transport coefficients, which agrees well with that observed experimentally, and in relating this to the strength of the association between an ion and its first coordination shell. The relationships between the various transport coefficients, such as those between the diffusion coefficient and the viscosity (Stokes-Einstein) and the conductivity (Nernst-Einstein) also exhibit composition dependences that reflect this association. The connection between the internal mobility and two measures of the coordination shell dynamics (the cage relaxation time and the self-exchange velocity) is explored; it is shown that the self-exchange velocity follows the composition and temperature dependence of the internal mobility very well. Finally, it is shown that allowing for anion polarization in the interaction model increases the mobility of all species without changing the structure of the melt discernibly, with the largest effect being found for the Li(+) ion.